2013
DOI: 10.1093/humrep/det032
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and functional preservation of pre-antral follicles after vitrification of macaque ovarian tissue in a closed system

Abstract: National Institutes of Health (NIH) Oncofertility Consortium UL1 RR024926 (1RL1-HD058293, HD058295, PL1 EB008542), the Eunice Kennedy Shriver NICHD/NIH (U54 HD018185) and ONPRC 8P51OD011092-53. G.M.F. works for the company that makes the polymers used in the current study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 2 publications
1
39
0
Order By: Relevance
“…As alternative methods to assess the viability of ovarian tissue, measuring the tissue's uptake of bromodeoxyridine during culture has been proposed. [59] To assess follicle viability, follicle isolation and 3D culture with evaluation of the follicle structures and diameter have been suggested [59].…”
Section: Discussionmentioning
confidence: 99%
“…As alternative methods to assess the viability of ovarian tissue, measuring the tissue's uptake of bromodeoxyridine during culture has been proposed. [59] To assess follicle viability, follicle isolation and 3D culture with evaluation of the follicle structures and diameter have been suggested [59].…”
Section: Discussionmentioning
confidence: 99%
“…At 5 months after transplantation, histological examination revealed the development of follicles and corpora lutea [16]. Similarly, Ting et al [17] assessed oocyte morphology after the vitrification of macaque ovarian tissue and concluded that it was a useful cryopreservation method. The reported compositions of the vitrification fluids used by the abovementioned groups for cryopreservation are shown in Table 1.…”
Section: Ovarian Tissue Cryopreservation By Vitrificationmentioning
confidence: 99%
“…The media created for Oncofertility Consortium Vitrification and Oncofertility Consortium Warming and Recovery kits were based on a previously established protocol for rhesus macaque ovarian tissue with modifications for ease of use as a kit and conversion to what would be needed for a clinical lab receiving human tissue [7,8] The CM for the Warming and Recovery kit is the same formulation as the Vitrification kit. The L-ascorbic acid 2-phosphate sesquimagnesium salt hydrate (AA2P, Sigma A8960) would be added to each medium by the end user and was kept as a lyophilized powder for a prolonged media shelf-life.…”
Section: Kit Componentsmentioning
confidence: 99%
“…Histology, proliferation, follicle counts, in vitro growth and hormone secretion in rhesus macaque [7] In vitro growth and hormone secretion of follicles isolated from vitrified rhesus macaque tissue [8] Examples of vitrification solutions that have been used for human, bovine, and non-human primate ovarian tissue preservation. A brief description of their analysis is listed.…”
Section: Kit Componentsmentioning
confidence: 99%
See 1 more Smart Citation